On conventional versus direct ageing of Alloy 718. (1st September 2018) - Theska, F.; Stanojevic, A.; Oberwinkler, B.; Ringer, S.P.; Primig, S.
Abstract: Alloy 718 is a Ni-based superalloy commonly used for parts of aircraft engines and power plants where very high demands on high-temperature yield strength, creep and corrosion resistance must be met. Polycrystalline parts such as turbine discs are industrially manufactured via hot-forging followed by solution annealing and dual ageing to form nanoscale γ′ and γ" precipitates. However, through the alternative process of 'direct ageing', increased yield strength contributions of ∼10% can be achieved while maintaining sufficient creep resistance. In addition to this so-called 'direct ageing effect', the omission of solution annealing between forging and ageing is economically attractive. Therefore, to date, direct ageing is widely implemented in the production of forged aerospace parts. However, the detailed mechanisms behind the direct ageing effect yet remain unclear. We present a correlative microscopy approach to identify the detailed microstructural evolution during conventional versus direct ageing. Our results confirm higher dislocation densities, lower δ-phase volume fractions and the absence of selected γ-matrix grain growth, as suggested in previous research. However, a key finding reported here via the use of atom probe microscopy is a remarkable structuring within and between the nanoscale γ′ and γ" precipitation. Not only do we find an increase in both the volume fraction and size of the γ" precipitates after direct ageing, we report a prevalence of stacked co-precipitation in various sequences depending on the nucleation condition. The findings are summarized in a microstructural model for conventional and direct ageing. Graphical abstract: Image 1